The Italian Code of Medical Deontology: characterizing features of its 2014 edition - Conti, Andrea Alberto (Acta Biomedica Atenei Parmensis, 2015)
The latest edition of the Italian Code of Medical Deontology has been released by the Italian Federation of the Registers of Physicians and Dentists in May 2014 (1). The previous edition of the Italian Code dated back to 2006 (2), and it has been integrated and updated by a multi-professional and inter-disciplinary panel involving, besides physicians, representatives of scientific societies and trade unions, jurisconsults and experts in bioethics....